Validation of a Visually Aided Dietary Assessment Tool to Estimate Dietary Intake in an Adult Swiss Population - Nève, Gilles; Bur, Laura; Lampert, Ladina; Höchsmann, Christoph; Brombach, Christine; Steinemann, Nina; Schmidt-Trucksäss, Arno (Frontiers in Nutrition, 2022)
Background Accurately assessing dietary intake is crucial for understanding how diet affects a person’s health. In large cohorts, paper-based dietary assessment tools (DAT) such as food recalls or food frequency questionnaires have emerged as valid tools with a low burden for participants. Objective To validate a visually aided DAT for use in studies with Swiss adults against the gold standard of a weighed 7-day food record (7 d-FR). Design Fifty-one adults (n = 24 women, n = 27 males) participated in the study and were recruited within two age groups (20–40 and 50–70 y). Each participant filled out the visually aided DAT, then the 7 d-FR. The DAT was compared to the 7 d-FR for total energy intake, macronutrients, sugar, water, and portions of fruits and vegetables. Pearson correlation and Bland–Altman analyses were used for statistical analyses. Results Total correlations ranged from 0.288 (sugar, p < 0.05) to 0.729 (water, p < 0.01). The older age group showed higher correlations for total energy intake, protein, fats, carbohydrates, and sugar, but not for water (p < 0.05). Correlations were moderate at r > 0.5, whereas only water and protein reached those values in the young group. Both groups overestimated total calories in kcal (+14.0%), grams of protein (+ 44.6%), fats (+36.3%), and portions of fruits and vegetables (+16.0%) but strongly underestimated sugar intake (−50.9%). Conclusion This DAT showed that all macronutrients and total energy intake were estimated more accurately by the older age group and therefore might be adequate to capture dietary habits in older Swiss adults.